The Frasnian-Famennian shelf deposits of the Bahram Formation in the Shams Abad section Kerman province, Central Iran: facies and sequence stratigraphy - hashmie, A; nikbakht, F; rezaee, P; ghorbanie, M; nejad, A rostam; zare, A (Sulaimani Journal for Pure and Applied Sciences, 2015)
Bahram Formation is a carbonate-clastic sequence of Late Devonian (Frasnian– Famennian) age and is deposited at the Central Iran sedimentary basin, Iran. In this investigation, Bahram Formation has been studied at Shams Abad section. Facies analysis and petrographic studies led to the recognition of 9 microfacies that are deposited in five facies belts: shore, tidal flat, lagoon, shoal and shallow open marine. The observed facies patterns indicate a mix carbonate-clastic shelf depositional environment. The shelf margin is formed as a result of tectonic activity associated with Hercynian orogeny passive margin in northeast Gondwana. Based on field observations, microfacies analysis and sequence stratigraphic concepts three, thirdorder sequences in this section. Sequences 3 joint with Hutk Formation (Carboniferous) are identified, on the basis of shallowing upward patterns. The transgressive deposits display a predominance of deep subtidal facies, while highstand deposits show shallow subtidal facies.
Keywords: Bahram Formation; FrasnianFamennian; Central Iran; Facies; Sequence stratigraphy